Konsep Islam Dalam Merehabilitasi Pecandu Narkoba - Khaer, Misbakhul (Spiritualita, 2018)
Khamer and all intoxicants (drugs and the like) are the culprits of all evil. The picture of the negative influence of drugs is so terrible. A person who consumes drugs can commit any crime, from the lightest crime to the most severe crime. Drug abuse is rampant in all circles, especially teenagers and children. Even though they are a generation of people who will replace the leadership relay in the future. Actually these concerns are also experienced by parents or families who have family members as victims of drug abuse, but most victimsâ€™ families do not know the solution to cure victims of drug addiction. Therefore, Islam as a natural religion is present to save them from the snares of drugs. Islam is truly present to position humanity in its noble place, birth and mind, soul and body both when they are alive and when they have died. The main points of Islamic teachings, such as prayer, fasting, charity and other services have many benefits and become the most effective therapy for body health, faith, intelligence, intelligence, and moral glory. The rehabilitative process is a continuation of the curative process. For drug addicts, by carrying out Islamic Shariâa teachings continuously (mudawamah) then by Allah SWT permission they will truly be released from the snares of drugs and their lives become more calm, peaceful, and comfortable. Islamic-style treatment methods for mental disorders and drug addiction become an alternative, even now many are used as references by the National Narcotics Agency. Because in addition to the method which is considered effective, easy, and simple also has no side effects compared to using medical rehabilitation methods. This method of treatment is merely an attempt and be aware to get healing. With full confidence that Allah SWT is the only One Who heals all kinds of diseases, there is no disease in this world that is not found in medicine, both physical and mental illness